Recent Advances in Photocatalytic Treatment of Palm Oil Mill Effluent (POME): A Review - Charles, Ashwin; Cheng, C. K. (Science Publishing Corporation, 2018)
Palm oil mill effluent (POME) pollution is a serious issue that has gained the attention of an international audience including policy makers, mill owners, NGOs and academicians. With a production rate of 74 million metric tonnes a year, Malaysia is in dire need for new technologies able to address this mounting problem. While previous research has attempted to modify existing microbial driven organic degradation methods to optimize the organic load removal, new studies recognize the futility in this endeavour as mills are unwilling to change the way they operate and adopt these disruptive technologies. Instead current research aims at tertiary polishing technologies of which photocatalysis has emerged as a forerunner. Recent advances indicate photocatalytic treatment of POME is a viable solution to the problem but for it to be cost effective, future studies should focus on visible light driven processes and new reactor configurations to improve the photocatalytic activity of existing systems.